A poly-L-lactic acid/ collagen/glycosaminoglycan matrix for tissue engineering applications. (September 2017) - Carfì Pavia, F; Ciappa, M; Lepedda, A; Fiorentino, SM; Rigogliuso, S; Brucato, V; Formato, M; Ghersi, G; La Carrubba, V
Adhesion of tissue cells to biomaterials is a prerequisite of paramount importance for the effectiveness of a tissue engineering construct (cell and scaffolds). Functionalization of polymeric scaffolds with organic polymers, such as collagen or proteoglycans, is a promising approach in order to improve the cytocompatibility. As a matter of fact, organic polymers, isolated directly from the extracellular matrix, contain a multitude of surface ligand (fibronectin, laminin, vitronectin) and arginine–glycine–aspartic acid-containing peptides that promote cell adhesion. In tissue engineering, the combination of organic and synthetic polymers gives rise to scaffolds characterized simultaneously by the mechanical strength of synthetic materials and the biocompatibility of natural materials. In this work, porous poly-L-lactide acid scaffolds were functionalized with a synthetic collagen–glycosaminoglycans matrix in order to improve cell adhesion. For this purpose, a protocol for collagen–glycosaminoglycans conjugation into the pores of the scaffolds was set up. Moreover, an innovative protocol for the quantification of the conjugated glycosaminoglycans inside the scaffolds was created and adopted. The results have confirmed the effectiveness of the developed protocol: a collagen–glycosaminoglycans conjugation, with an efficiency of about 21% was obtained inside the scaffold. Moreover, SEM analysis highlighted the presence of the homogeneous synthetic matrix into the bulk of porous scaffolds. Finally, cell culture assays carried out by utilizing mouse embryonic fibroblasts showed that cell proliferation on poly-L-lactide acid-collagen–glycosaminoglycans scaffold is higher than on poly-L-lactide acid collagen scaffold (utilized as control). Therefore, it can be stated that the presence of glycosaminoglycans not only increases the mechanical strength of the matrix, thanks to their cross-linking effect, but also it seems to lead to a more significant cell growth. Overall, it is reasonable to state that the concerned protocol may be proposed as a reliable route to increase the rate of proliferation and in some cases to stimulate the cell differentiation in tissue engineering devices.